Low prevalence of syphilis infection among key populations in Togo in 2017: a national cross-sectional survey - Didier K. EKOUEVI; Alexandra M. BITTY-ANDERSON; Fifonsi A. GBEASOR-KOMLANVI; Yao R. KONU; Essèboè K. SEWU; Mounerou SALOU; Claver A. DAGNRA (BMC, 2019)
Abstract Background The World Health Organisation (WHO) recommends the screening of syphilis among populations highly exposed to HIV. However, data on the prevalence of syphilis in these populations are scarce in Togo. This study aimed at estimating the prevalence of syphilis among males who have sex with males (MSM), female sex workers (FSW) and drug users (DU) in Togo. Methods A cross-sectional bio-behavioral study was conducted in August and September 2017 using a respondent-driven sampling (RDS) method in eight major cities in Togo. A standardized questionnaire was used to record socio-demographic data and sexual behavior patterns. A blood sample was taken and SD Bioline Duo VIH/Syphilis rapid test was used to test for HIV and syphilis. Results A total of 2158 key populations (678 MSM, 1003 FSW and 477 DU), with an average age of 27.6 years (standard deviation 8.8 years) participated in the study. Prevalence of syphilis was 0.6% (95% CI = [0.3-1.0]) with no statistical significance between the three groups: null among MSM, 0.8% among FSW (95% CI = [0.37-1.63]) and 1.1% among DU (95% CI = [0.39-2.57]). There was no relation between HIV status and syphilis (p = 0.236). Among the 298 HIV-positive people, none was diagnosed with syphilis. Conclusions Findings from this study reveal a low prevalence rate of syphilis among key populations in Togo. Specific interventions into HIV prevention programs should be reinforced to eliminate syphilis in Togo.